PENERAPAN MODEL PEMBELAJARAN TEAM GAMES TOURNAMENT UNTUK MENINGKATKAN KETERAMPILAN KOLABORASI PESERTA DIDIK KELAS 4 SDN KALIRUNGKUT 1/264 SURABAYA - Siti Mualifah; Roni Rodiyana; Yuni Purwanti; Slamet Mulyadi; Dwi Wahyuni Maulidiyah (STKIP Subang, 2024)
This research aims to improve the Collaboration skills of fourth-grade elementary school students by implementing the Teams Games Tournament (TGT) model. This study is a Classroom Action Research (CAR) which was conducted in two cycles with the following steps: 1) Planning; 2) The implementation of the TGT model and observation; 3) Reflection of each cycle. Data collection techniques use observation and documentation techniques to see students' collaborative skills. The research instruments are observation sheets, and rubrics. Data analysis techniques use quantitative descriptive analysis techniques to describe students' collaborative skills. The subject of this study is 27 fourth-grade students of Elementary School Kalirungkut 1/264, Surabaya. The results showed improved collaborative skills in every cycle (pre-cycle, cycle 1, and cycle 2). The average collaborative skills of the pre-cycle amounted to 58, cycle 2 increased to 68, and cycle 2 increased to 80. Based on the results, it can be concluded that implementing the Teams Games Tournament (TGT) models can improve collaborative skills. Keywords: Teams Games Tournament, Collaborative skills